2021
DOI: 10.1371/journal.pone.0245107
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of the Val66Met polymorphism in musicians: Possible evidence for compensatory neuroplasticity from a pilot study

Abstract: The study compared the prevalence of the Val66Met Brain-derived Neurotrophic Factor single nucleotide polymorphism (rs6265) in a sample of musicians (N = 50) to an ethnically matched general population sample from the 1000 Human Genome Project (N = 424). Met-carriers of the polymorphism (Val/Met and Met/Met genotypes) are typically present in 25–30% of the general population and have associated deficits in motor learning and plasticity. Many studies have assessed the benefits of long-term music training for ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…51 A decrease in BDNF production caused by the Val66Met BDF single-nucleotide polymorphism rs6265, present in 25%-30% of the population, is associated with prolonged initiation and termination of SWA (a type of EEG oscillation present primarily during NREM that is enhanced proportionally by the duration of wake time preceding sleep, a marker of sleep need). [52][53][54] Moreover, those individuals display reduced SWS duration and sleep activity (as measured by delta activity). 54 In a study on patients with major depressive disorder, it was revealed that upregulated BDNF production was linked to more intense SWA and higher NREM sleep quality; however, the level of this neurotrophin did not bear any relation to insomnia in this group.…”
Section: Bdnf and Sleep Regulationmentioning
confidence: 99%
“…51 A decrease in BDNF production caused by the Val66Met BDF single-nucleotide polymorphism rs6265, present in 25%-30% of the population, is associated with prolonged initiation and termination of SWA (a type of EEG oscillation present primarily during NREM that is enhanced proportionally by the duration of wake time preceding sleep, a marker of sleep need). [52][53][54] Moreover, those individuals display reduced SWS duration and sleep activity (as measured by delta activity). 54 In a study on patients with major depressive disorder, it was revealed that upregulated BDNF production was linked to more intense SWA and higher NREM sleep quality; however, the level of this neurotrophin did not bear any relation to insomnia in this group.…”
Section: Bdnf and Sleep Regulationmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) revealed the association of rs9854612 (GATA2, 3q21.3,), rs13146789 and rs13109270 (PCDH7, 4p15.1) with music perception [5]; whereas transcriptome-based analyses demonstrated a differential expression of α-synuclein gene (SNCA, 4q22) while listening to classical music [10,14,15,16]. Some studies implicated neuronal plasticity genes, for instance, brain-derived neurotrophic factor (BDNF) [17] and GRIN2B genes [1] to be related to music ability.…”
mentioning
confidence: 99%
“…Some studies implicated neuronal plasticity genes, for instance, brain-derived neurotrophic factor (BDNF) [17] to be related to music ability. Musical talent can be partially attributed to the efficacy of innate ability for motor and sensory learning to play musical instruments.…”
mentioning
confidence: 99%
See 1 more Smart Citation